Combined use of radiocarbon and stable carbon isotopes for the source mixing model in a stream food web. (6th July 2020) - Ishikawa, Naoto F.; Finlay, Jacques C.; Uno, Hiromi; Ogawa, Nanako O.; Ohkouchi, Naohiko; Tayasu, Ichiro; Power, Mary E.
Abstract: Radiocarbon natural abundance (Δ 14 C) has emerged as a useful dietary tracer in freshwater ecology for the past decade, yet its applicability for separating aquatic and terrestrial resources has not been examined quantitatively. Here, we report Δ 14 C values of stream invertebrates in different functional feeding groups collected from the upper South Fork Eel River watershed, northern California. We found that algae‐grazing insect larvae show low Δ 14 C values (−43.1 ± 21.8‰, mean ± standard deviation, N = 6), reflecting the signal of dissolved inorganic carbon weathered from ancient inorganic carbon or respiration of old organic carbon. In contrast, the Δ 14 C values of leaf‐shredding insect larvae (21.7 ± 31.9‰, N = 5) were close to those of contemporary atmospheric CO2 except at the SF Eel River where algal production was highest. The Δ 14 C values of predators (−6.1 ± 35.7‰, N = 14) were intermediate between those of grazers and shredders. In a Bayesian mixing model, Δ 14 C provided a more ecologically realistic estimate for terrestrial vs. aquatic source contributions to invertebrates with lower uncertainty (i.e., narrower credible interval) than did the stable carbon isotopes (δ 13 C). These results demonstrate that Δ 14 C can be used, in combination with δ 13 C, to more precisely estimate organic matter sources to stream animals.